Recurrent Endophthalmitis after Trabeculectomy for Glaucoma: Importance of Timely Filtering Bleb Coverage for the Conjunctiva - Carl-Ludwig Schönfeld (Case Reports in Ophthalmology, 2012)
Purpose: To report the occurrence of endophthalmitis after trabeculectomy for glaucoma that was treated by vitrectomy without bleb closure and recurred 3 times after an initial clinically inapparent period of about 2 years. Methods: Interventional case report and short review of the pertinent literature. Results: A 73-year-old Caucasian female underwent trabeculectomy (without mitomycin) for glaucoma. Four years after the trabeculectomy, an endophthalmitis with Staphylococcus epidermidis as the causative organism occurred and was treated with a pars plana vitrectomy (20-gauge) and a combined antibiotic and anti-inflammatory drug regimen. The bleb was not covered during the emergency procedure because the filtering bleb was heavily infected and filled with pus. As the filtering bleb healed nicely and the filtering function was restored, the filtering bleb was left as it was, and best-corrected visual acuity initially recovered to 0.8. After 22 months, the endophthalmitis recurred, this time with Enterococcus faecalis as the causative organism. Its treatment required a total of four further vitrectomies (23-gauge), each accompanied by the same antibiotic and anti-inflammatory drug regimen that had been applied previously. However, the visual acuity could not be preserved, and the eye is blind with defective light projection. Conclusions: The literature suggests an aggressive surgical approach to endophthalmitis, and the present case report confirms this. Since the visual prognosis of eyes after endophthalmitis is poor, the course of treatment for endophthalmitis after trabeculectomy should emphasize recurrence prophylaxis rather than address glaucoma symptoms and therefore include safe bleb leak coverage.